lmrrege
contestada

When deriving the Law of Cosines, the equation h^2=a^2-x^2 is created using the Pythagorean theorem. Use substitution to replace h2 in the equation below and then simplify. c^2=h^2+b^2-2bx+x^2

Respuesta :

Answer:

[tex]c^2=a^2+b^2-2bx[/tex]

Step-by-step explanation:

We are given equation

[tex]h^2=a^2-x^2[/tex]

we need to plug this equation into

[tex]c^2=h^2+b^2-2bx+x^2[/tex]

we can replace h^2

and we get

[tex]c^2=a^2-x^2+b^2-2bx+x^2[/tex]

now, we can cancel like terms

[tex]c^2=a^2+b^2-2bx[/tex]

so, we get after simplification as

[tex]c^2=a^2+b^2-2bx[/tex]


Answer:

A) c^2=a^2+b^2-2bx

Step-by-step explanation:

got it right on edge :)